This I Believe - Cousins, Norman (Tufts Archival Research Center, 2006)
Norman Cousins describes his beliefs in both the individuality of the self and the unity of all humanity, as well as in a moral order derived from universal order; therefore, the poverty of others impacts his own condition, and he works to alleviate social problems.